2022
DOI: 10.21037/cdt-22-155
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of N-terminal pro-form B-type natriuretic peptide (NT-proBNP) in patients with congenital heart disease undergoing cardiac surgery: a systematic review and meta-analysis of cohort studies

Abstract: Background: To perform an updated and comprehensive meta-analysis on the prognostic value of N-terminal pro-form B-type natriuretic peptide (NT-proBNP) in patients with congenital heart disease (CHD) undergoing cardiac surgery.Methods: A systematic search was conducted until September 2021 for relevant studies published in PubMed, Web of Science Database and Embase. Based on the average values, NT-proBNP concentrations were classified as high and low levels. The outcomes of interest were mortality, cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Incidence of an acute kidney injury (AKI) in patients undergoing heart valve surgery is a fairly common complication observed in the early postoperative period, occurring with a frequency of about 3 to 34% [5,15,16]. Despite constant progress in intensive care, nephrology and dialysis, mortality in acute kidney injury remains high-in the presented study, out of 50 patients with postoperative AKI requiring renal replacement therapy, inhospital death occurred in 38 patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Incidence of an acute kidney injury (AKI) in patients undergoing heart valve surgery is a fairly common complication observed in the early postoperative period, occurring with a frequency of about 3 to 34% [5,15,16]. Despite constant progress in intensive care, nephrology and dialysis, mortality in acute kidney injury remains high-in the presented study, out of 50 patients with postoperative AKI requiring renal replacement therapy, inhospital death occurred in 38 patients.…”
Section: Discussionmentioning
confidence: 79%
“…So far, the available literature lacks clear information on the predictive ability of the preoperative Nt-proBNP level in predicting the occurrence of postoperative AKI requiring renal replacement therapy in patients undergoing heart valve surgery. It has been shown that an increased level of Nt-proBNP is an independent predictor of the occurrence of postoperative AKI in the general group of adult patients treated with cardiac surgery as well as in the pediatric group; otherwise, it has been demonstrated that elevated Nt-proBNP values are associated with a prolonged stay in an intensive care unit after cardiac surgery for congenital heart defects [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…IGF-1 is a peptic hormone that has been connected to various cardiovascular diseases, where higher serum levels show to have cardioprotective effects (improves cardiomyopathy, modulates myocardial remodeling post-infarction…), while lower serum levels are associated with unfavorable cardiac outcome. 19 Only three patients (6.2%) had abnormal values in this study and, consequently, the number was underpowered to establish an association between the biomarker and morphological or hemodynamic changes. NT-proBNP has been identified as a marker of HF and its prognostic value in CHD is currently under investigation.…”
Section: Biomarkersmentioning
confidence: 87%
“…In previous studies, researchers have sought strongly to elaborate the postoperative prognostic value of NT-proBNP in pediatric CHD patients 18 . Most studies focused on early postoperative outcomes, and the results showed that NT-proBNP had significant predictive value for longer ICU stay and mechanical ventilation, inotropic support, and acute kidney injury 19 22 .…”
Section: Discussionmentioning
confidence: 99%